WAYS TO IMPROVE THE ACTIVITIES OF JOINT-STOCK COMPANIES IN THE CAPITAL MARKET (European Journal of Economics, Finance and Business Development, 2025)
This article explores practical and strategic ways to improve the activities of joint-stock companies in the capital market, focusing on strengthening their financial position, transparency, and investor attractiveness. In the context of global financial integration and increasing investor demands, joint-stock companies must adopt advanced mechanisms to ensure effective participation in capital markets. The study analyzes key improvement areas, including enhancing corporate governance, improving disclosure and reporting standards, optimizing capital structure, and diversifying financial instruments. Emphasis is placed on the importance of digital transformation, regulatory compliance, and building investor confidence through sustainable financial practices. Using comparative and empirical methods, the research draws insights from both developed and emerging market economies to outline successful strategies. The findings suggest that proactive engagement in the capital market not only boosts market capitalization and share liquidity but also contributes to long-term value creation for shareholders. The article concludes by presenting a policy-oriented framework for increasing the operational effectiveness of joint-stock companies in dynamic capital market environments.